2020
DOI: 10.3390/molecules25225339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grape Polyphenols on the Life Span and Neuroinflammatory Alterations Related to Neurodegenerative Parkinson Disease-Like Disturbances in Mice

Abstract: Functional nutrition is a valuable supplementation to dietary therapy. Functional foods are enriched with biologically active substances. Plant polyphenols attract particular attention due to multiple beneficial properties attributed to their high antioxidant and other biological activities. We assessed the effect of grape polyphenols on the life span of C57BL/6 mice and on behavioral and neuroinflammatory alterations in a transgenic mouse model of Parkinson disease (PD) with overexpression of the A53T-mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 49 publications
1
10
0
1
Order By: Relevance
“…In this work, we have demonstrated for the first time that CJ treatment decreased α-synuclein expression in the midbrain of rats co-treated with CJ and ROT. Experimental evidence has shown that rich in PACs grape products significantly decreased the α-synuclein accumulation in the frontal cortex of transgenic mice with overexpression of the A53T-mutant human cells [ 37 ] and in ROT-treated human neuroblastoma-derived cells [ 36 ]. Oxidative stress is suggested to play a crucial role in PD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we have demonstrated for the first time that CJ treatment decreased α-synuclein expression in the midbrain of rats co-treated with CJ and ROT. Experimental evidence has shown that rich in PACs grape products significantly decreased the α-synuclein accumulation in the frontal cortex of transgenic mice with overexpression of the A53T-mutant human cells [ 37 ] and in ROT-treated human neuroblastoma-derived cells [ 36 ]. Oxidative stress is suggested to play a crucial role in PD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids have been shown to reverse cognitive impairments and inhibit the progression of Alzheimer's disease, implying that they may have therapeutic potential [ 105 ]. Flavonoid-rich diets including grape juice, cocoa, and blueberry are used as memory enhancers [ 82 , 106 , 107 ]. In a randomized controlled clinical study, daily ingestion of anthocyanin-rich cherry juice improved fluency, short-term memory, and long-term memory in aged people (70+) with dementia [ 108 ].…”
Section: Role Of Flavonoids In Neuroprotectionmentioning
confidence: 99%
“…Grape is an evident example of fruits that contain a high content of polyphenols [59]. Dietary supplement of grape polyphenol concentrate at 1.5 mL/kg significantly enhanced memory reconsolidation in transgenic mouse model of PD [60]. Curcumin is a polyphenol present in turmeric (Curcuma longa) root, which is a yellow pigment used in curry.…”
Section: Polyphenols In Neurodegenerative Diseasesmentioning
confidence: 99%